CURRENCY EXCHANGE RATE PREDICTION USING MACHINE LEARNING TECHNIQUES - manjit Das , Mohammed Siddique (International Journal of Modern Agriculture, 2020)
The financial status of any nation measured on different parameters, the value of foreign currency is one of the major factors. The economical condition of any nation signifies from its currency value in international market. The international market deals with United States Dollar as standard currency for any kind of international transactions but currencies like EURO etc are also popular in international market. We can say if our nation currency is less than the international standard currency then our economy is not good. The value of currency makes changes depending of many factors and conditions. So it makes more challenging to predict the value of our currency in international standard like US Dollar or EURO. This paper introduces a machine learning model to predict the exchange rate of foreign currency values with respect to Indian rupees. The efficiency of the proposed model is measured and validated using standard performance measured techniques like MAPE, MAE and MSE. The performance of the proposed model is good enough to be accepted.